Analisis Tindak Tutur pada Pembelajaran Bahasa Indonesia Kelas XI MIPA 1 UPT SMA Negeri 14 Jeneponto - Ratih Yuni Puspita; Sitti Rabiah; Ihramsari Akidah (Journal on Education, 2023)
This study aims to describe (1) It is very important to use directive speech acts during the teaching and learning process at school. Therefore, it is necessary to pay attention to the use of directive speech acts uttered by the teacher during the lesson. (2) This type of research is descriptive qualitative research. The subjects of this study were teachers who teach Indonesian at UPT SMA Negeri 14 Jeneponto. While the informants in this study were teachers who taught Indonesian for class XI Mipa 1 UPT SMA Negeri 14 Jeneponto. The results of research on the forms and functions of teacher directive speech acts in Indonesian language learning class XI Mipa 1 UPT SMA Negeri 14 Jeneponto show that the use of command directive speech acts and functions of command directive speech acts is the most widely used compared to other directive speech acts. This can be seen from the results of the research which showed that the form of command speech acts and the function of command speech acts were used by Indonesian teachers, namely 10 utterances. The forms of directive speech acts found are directive speech acts of commands, requests, granting permission, advice, questions and prohibitions.